Gender-specific association between the blood pressure category according to the updated ACC/AHA guidelines for hypertension and cardio-ankle vascular index: a community-based cohort study. Issue 5 (May 2020) - Kamon, Tatsuya; Kaneko, Hidehiro; Itoh, Hidetaka; Kiriyama, Hiroyuki; Mizuno, Yoshiko; Morita, Hiroyuki; Yamamichi, Nobutake; Komuro, Issei
Highlights: Age and cardiovascular disease risk factors increased with blood pressure (BP) category in both males and females. Cardio-ankle vascular index (CAVI) ≥9 increased with BP category in males, but not in females. BP category was independently associated with CAVI ≥9 in males, but not in females. Abstract: Background: The American College of Cardiology (ACC)/American Heart Association (AHA) guidelines for hypertension have lowered the threshold of normal blood pressure (BP). However, how this updated guideline should be applied to the general population is still under debate, and may depend on gender because of a substantial gender difference in the risk of cardiovascular disease. We aimed to clarify the gender difference in the association between BP category and cardio-ankle vascular index (CAVI), as a marker of subclinical atherosclerosis, using a community-based cohort. Methods: We examined 1, 241 subjects (699 males and 542 females) who underwent health check-ups at our institute. We defined normal pressure as systolic (s)BP <130 mmHg and diastolic (d)BP <80 mmHg, stage 1 hypertension as 130 mmHg ≤ sBP < 140 mmHg or 80 mmHg ≤ dBP <90 mmHg and stage 2 hypertension as sBP ≥140 mmHg or dBP ≥90 mmHg, including subjects on antihypertensive medications. High CAVI was defined as CAVI ≥9.0. Results: Age and the prevalence of most of atherosclerotic risk factors increased with increasing BP category in both male and female subjects. A linear relationship between the prevalence of high CAVI and high BP category was observed in males, but not in females. Multivariable logistic regression analysis revealed that BP category was independently associated with high CAVI in males but not in females. Conclusion: There was a difference seen between males and females in the association between BP category, according to the updated ACC/AHA guideline, and CAVI, suggesting that the optimal management strategy for hypertension may depend on not only age, obesity, and diabetes mellitus, but also gender.